O-GlcNAcylation Links ChREBP and FXR to Glucose-Sensing - Benhamed, Fadila; Filhoulaud, Gaelle; Caron, Sandrine; Lefebvre, Philippe; Staels, Bart; Postic, Catherine (Frontiers in Endocrinology, 2015)
Accumulating evidence suggests that O-GlcNAc transferase (OGT), an enzyme responsible for O-GlcNAc post-translational modification acts as a nutrient sensor that links glucose and the hexosamine biosynthetic pathway to the regulation of transcriptional factors involved in energy homeostasis. In liver, glucose signaling is mediated by ChREBP (carbohydrate response element binding protein) which stimulates glycolytic and lipogenic gene expression through its binding on a specific ChoRE DNA sequence. Modulation of ChREBP by O-GlcNAcylation increases its DNA binding affinity and its activity. ChREBP transcriptional activity also depends on the presence of several other co-factors and transcriptional factors. Among them, the nuclear Farnesoid X Receptor (FXR), a key transcription factor of bile acid metabolism involved in the gut-liver axis homeostasis was recently shown to directly interact with ChREBP, acting as a repressor on the ChoRE of glycolytic genes. Interestingly, similarly to ChREBP, FXR is O-GlcNAcylated in response to glucose. This review discusses the importance of ChREBP and FXR modification through O-GlcNAcylation in liver and how glucose can modify their mutual affinity and transcriptional activity.